Respuesta :

Answer:

  an = 22 -6(n -1)

Step-by-step explanation:

The first term of the sequence is given as a1 = 22. The general term of an arithmetic sequence is ...

  an = a1 +d(n -1) . . . . n-th term for first term a1 and common difference d

The third term will be ...

  a3 = 10 = 22 +d(3 -1)

Then the common difference is ...

  10 -22 = 2d

  -12/2 = d = -6

__

Putting the known values into the formula for the general term, it becomes ...

  an = 22 -6(n -1)

__

This can be simplified to ...

  an = 28 -6n